Overview of the CEAMMC PureData distribution and library - Poltavsky, Serge; Nadzharov, Alex (Revista Vórtex, 2021)
This text is a report about the CEAMMC PureData distribution - also known as “Pd-ceammc” - and the CEAMMC external library for the official Pure Data distribution by Miller Puckette - also known as “Pd Vanilla”. The CEAMMC Pure Data repository is available at https://github.com/uliss/pure-data. This distribution is a software package that comprises the original Pure Data distribution with several user interface enhancements and the CEAMMC object library plus yet other external libraries. The CEAMMC library itself is also available via the Deken package manager so it can be installed in Pd Vanilla. This paper focuses on our main concepts for this work, current features and future plan.